THE DIALECTIC OF HADITH BETWEEN SALAFI-SUFI AND ITS INFLUENCE ON RELIGIOUS PRACTICE IN WEST SUMATRA - Nofri Andy.N; Ja’far Assagaf; Kamaluddin Nurdin Marjuni (Penamas, 2024)
The understanding of the hadith becomes diverse when it is read and understood from different perspectives. The condition is static when the hadith is understood textually but will become elastic when approached and analyzed with a ta'wil approach. This study aims to reveal the salafi-sufi hadith and its influence on religious practices in West Sumatra. The method used is descriptive analysis by revealing the Salafi and Sufi ways and then analyzing the character so that it has an impact on differences in religious practice. The results showed that the differences in views in understanding the hadith were due to efforts to legitimize religious authority, the textual salafi group did not open space to develop a text but on the other hand the Sufis who tended to use the construction of kasyf accommodated the value of locality so that it affected religious practice both in terms of perspective and attitude.